Rehabilitation of speech in Parkinson's disease - Strojek, Katarzyna; Karpińska, Anna; Kaźmierczak, Urszula; Zukow, Walery; Radzimińska, Agnieszka (Journal of Education, Health and Sport, 2017)
Parkinson's disease in spite of being nowadays considered as an inauspicious health prognosis because of its incurable nature, can be combated by the use of a number of non-pharmacological methods. With their help a patient will be able to retain full independence and mobility as long as possible. The immediate cause of the disease is a disorder of the proper functioning of the extrapyramidal system, which is associated with the occurrence of characteristic symptoms such as dysfunction of the musculoskeletal system and the autonomic nervous system, abnormal sensation and mental disorders. Planning of the improvement is guided by the presence of the primary symptoms such as muscle rigidity, slowness of movement and tremor. One of the effects of the co-occurrence of these symptoms are speech disorders. There is a number of characteristic features for speech disorders of a person with Parkinson's disease and they mainly concern its quality. These dysfunctions negatively affect the patient's communication with the environment. Properly implemented physical activity brings beneficial results, causing a delay in the buildup of disease symptoms.